Investigation of polyethylenimine/DNA polyplex transfection to cultured cells using radiolabeling and subcellular fractionation methods - Shi, Julie (2013)
Quantitative analysis of the intracellular trafficking of non-viral vectors provides critical information that can guide the rational design of improved cationic systems for gene delivery. Subcellular fractionation methods, combined with radiolabeling, produce quantitative measurements of the intracellular trafficking of non-viral vectors and the therapeutic payload. In this work, differential and density-gradient centrifugation techniques were used to determine the intracellular distribution of radiolabeled 25 kD branched polyethylenimine (bPEI)/plasmid DNA complexes (“polyplexes”) in HeLa cells over time. By differential centrifugation, [(14)C]bPEI was found mostly in the lighter fractions whereas [(3)H]DNA was found mostly in the heavier fractions. A majority of the intracellular polymer (~60%) and DNA (~90%) were found in the nuclear fraction. Polymer and DNA also differed in their distribution to heavier and denser organelles (lysosomes, mitochondria) in density-gradient centrifugation studies. An unexpected finding from this study was that between 18–50% of the DNA applied to the cells became cell-associated (either with the cell membrane and/or internalized), while only 1–6% of the polymer did so, resulting in an effective N/P ratio of less than 1. These results suggest that a significant amount of cationic polymer is dissociated from the DNA cargo early on in the transfection process.